Bone Marrow Reticulin Content In Acute Leukemia - Jalal, Eman Sadiq (Journal of the Faculty of Medicine Baghdad, 2006)
Background: Increase in marrow reticulin has long been recognized in primary myelofibrosis, but little was known about the reticulin structure of leukemic marrows, there has been a tendency to accept an increase in marrow reticulin as evidence of myelofibrosis. Similarly, there has been a tendency to diagnose as "acute myelofibrosis" cases of acute leukemia with brisk reticulin and early collagen production. This study was undertaken to determine incidence, type and pattern of fibrosis in the bone marrow of patients with acute leukemia, both acute lymphoblastic and acute myeloid leukemia. Method: thirty-five bone marrow biopsy specimens from patients with acute leukemia were examined histologically; connective tissue stains were applied for stromal studies. Result: an increase in marrow reticulin is common at presentation in patients with acute leukemia, effective anti-leukemic therapy results in resolution of the increased marrow reticulin. Conclusion: The reticulin type of fibrosis is the common type encountered in acute leukemia which is of diffuse pattern, higher incidence of bone marrow fibrosis in patients with acute lymphoblastic leukemia than those with acute myloid leukemia. Fiber bone formation is found in 10% of cases of acute lymphoblastic leukemia ,but is not extensive and well developed as in cases of primary myelofibrosis.